2016
DOI: 10.4172/2169-0022.1000314
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Physico-Chemical, Thermal and Mechanical Properties of Sintered Graphite and Mesophase Formulations

Abstract: Carbon/graphite materials are widely applied to the areas of seal and friction materials. These applications exploit the exceptional properties of carbon/graphite, such as its excellent mechanical behavior at high temperature and low reactivity. However, Owing to high open porosity, and low strength conventional carbon/graphite materials prepared using pulverized coke as filler and pitch as binder fall across enormous challenge. Therefore, it is necessary to reduce the open porosity and increase in the strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In this way, the surface of the titanium in an acid medium will remain positively charged and negatively charged in an alkaline medium. It has been reported that titanium dioxide has a higher oxidizing activity at a lower pH, but the excess of H + ions can decrease the reaction rate [26].…”
Section: Choice Of Reaction Conditionsmentioning
confidence: 99%
“…In this way, the surface of the titanium in an acid medium will remain positively charged and negatively charged in an alkaline medium. It has been reported that titanium dioxide has a higher oxidizing activity at a lower pH, but the excess of H + ions can decrease the reaction rate [26].…”
Section: Choice Of Reaction Conditionsmentioning
confidence: 99%
“…The resistivity and high-temperature resistance enable the graphite to be used for refractory materials, batteries and other fuel cells [ 1 ]. Graphite is the material ensuring efficient lubrication so, it can be used for electric motors brushes and sealing materials [ 2 ]. In such cases, the carbon material is compacted under a high compressive load and the measurements are being made on the ready to use products [ 3 ].…”
Section: Introductionmentioning
confidence: 99%